The Impact of Hidden Costs on Production and Operations - Uma Bhushan; Rajashree Gujarathi; Arindam Banerjee; Himanshu Sharma; A. Seetharaman (Journal of Accounting, Business and Management (JABM), 2017)
The paper is a conceptual research in hidden costs which are increasing important in the everchanging technology world. The worldwide manufacturing environment has evolved rapidly from only producing a narrow range of products to a wide range of customized products. While the world’s attention is focused on the fight to increase productivity and develop new technologies to maintain manufacturing competitiveness, the change in this nature has called for a serious review of the existing cost management strategy and lead to intense focus on the less visible but every bit as critical to the cost incurred by the hidden factory of offline transactions. This paper identifies various elements and contributing factors of common hidden costs in production and associates the impact to the total product cost. Hidden costs cannot be eliminated completely but can be reduced. Hidden costs transform from one area to another and sometime they are essential parts of the manufacturing costs. This paper also discusses a case study on offshore outsourcing by using transactional cost analysis to reveal the additional hidden costs associated with the transaction where traditionally, people like to associate cost to physical units or activities, but not on the exchange of transaction. As the demand in hidden cost analysis increases, managers are aware that the existing cost system and direct allocation method is not capable to provide accurate cost information to help the cost reduction effort. Hence, classification of hidden costs and ability to transform them into visible cost becomes critical.